Binding of cholesterol by Neisseria gonorrhoeae. - Miller, R D (1978)
The binding of [1,2-3H]cholesterol to Neisseria gonorrhoeae CS-7, Pseudomonas aeruginosa, and Salmonella typhimurium (smooth and rough strains) was investigated. The kinetics of cholesterol binding to N. gonorrhoeae CS-7 demonstrated that binding occurred slowly with maximum binding by 10 h. Under optimum conditions, a large percentage (65%) of the added cholesterol was associated with the cells. Chemical fractionation revealed that ca. 98% of the labeled cholesterol was associated with the cell membrane(s). The bound cholesterol was not esterified and was associated primarily with the cytoplasmic membrane. Intact gonococci bound 4 to 30 times more cholesterol than the deep rough mutant S. typhimurium TA1535, the wild-type S. typhimurium DB-21, and P. aeruginosa. In contrast, isolated cell membranes from all organisms rapidly bound cholesterol to the same extent. Therefore, the outer membrane can function as a permeability barrier to cholesterol. Cholesterol binding to both whole cells and isolated cell membranes was influenced by the incubation temperature. The rate of cholesterol binding by whole cells of N. gonorrhoeae decreased markedly at lower temperatures, with almost complete cessation of binding at 0 degrees C. A similar temperature effect on the binding of cholesterol to isolated membranes was not observed. Thus, the effect of temperature on the binding of cholesterol to whole cells was an effect not on the actual binding process but rather on the ability of the cholesterol molecule to penetrate the lipid domain of the gonococcal outer membrane.